Improving the Visible Light Photocatalytic Aerobic Oxidation of Sulfides into Sulfoxides on Dye‐Sensitized TiO2. Issue 20 (13th September 2018) - Hao, Huimin; Wang, Zhan; Shi, Ji‐Long; Li, Xia; Lang, Xianjun
Abstract: Visible light‐driven interfacial redox reactions during dye‐sensitized TiO2 are essential to meet the energy and environmental challenges in the form of dye‐sensitized solar cells and sensitized degradation of organic pollutants. Inspired by these prior successes, it is conceivable that the underlying principles of these processes can guide us to construct selective chemical transformations in which the control of selectivity is in higher demand. We attempt to improve the selectivity for sulfoxides during the visible light‐driven selective aerobic oxidation of sulfides in the merger of dye‐sensitized TiO2 photocatalysis with TEMPO [(2, 2, 6, 6‐tetramethylpiperidin‐1‐yl)oxyl] catalysis. Thus, different factors like the TEMPO and its derivatives, initial O2 pressures, initial sulfide concentrations, solvents, light‐emitting diodes (LED) and TiO2 were examined to identify the critical factor for selectivity improvement. It was found that an easily synthesized anatase TiO2, sensitized by 0.33 mol % of alizarin red S, was significant in improving the selectivity for sulfoxides at high conversions of sulfides with the aid of 2 mol % of TEMPO as a redox mediator under blue LED irradiation. This work suggests that the engineering of the TiO2 materials can be a viable solution in improving the selectivity of visible light‐driven chemical transformations by dye‐sensitized TiO2 photocatalysis. Abstract : Oh, it's titania. TiO2 is important to improve the selectivity to sulfoxides and the reaction rate of the visible‐light‐induced selective oxidation of sulfides with air during the merger of dye‐sensitized TiO2 photocatalysis with TEMPO catalysis. It was found that an easily synthesized anatase TiO2, sensitized by 0.33 mol % of alizarin red S, has significantly improved selectivity to sulfoxides at high conversions of sulfides with 2 mol % of TEMPO as a co‐catalyst under blue LED irradiation.